SOSIALISASI LITERASI MOTORIK BAGI PESERTA DIDIK SEKOLAH MENENGAH PERTAMA - jarwo, sujarwo (Empowerment: Jurnal Pengabdian pada Masyarakat, 2022)
This activity aims to provide education to junior high school students in Yogyakarta about the new junior high school curriculum and also the motor literacy of junior high school children. Lecturer activities outside the campus are also one of the tri dharma activities of lecturers in Higher Education to always promote science and technology so that it is beneficial to the public. This method of lecturer service activities outside the campus is carried out on June 24, 2022. Lecturers' activities outside the campus are carried out face-to-face (offline) in the Audio Visual room of State Junior High School 9 Yogyakarta. The target audience in this activity was focused on 35 junior high school students. The criteria for the success of this activity are that the knowledge of junior high school students about the prototype curriculum and motor literacy has increased, with a minimum score of 70. Data analysis used a different test/t test by comparing the mean test results. The results of the pre test showed that the average knowledge of students at State Junior High School 9 Yogyakarta was at an average mean: 54, after being given material by a team of lecturers doing off-campus activities there was an increase in the mean: 79. Motor literacy socialization activities for students in junior high school able to provide additional knowledge to the audience of participants in knowing motor literacy in physical education learning.